Research on Consumer Purchasing Channel Choice Based on Product Tolerance: The Mediating Role of Rationalization - Chen, Jinsong; Wu, Yumin; Jiang, Xue (Frontiers in Psychology, 2022)
Consumers have subjective psychological expectations of the quality and brand of products before purchasing. There is a certain tolerance for products that do not meet expectations. The discomfort caused by tolerance can be smoothly carried out through “reasonable” self-comfort and explanation mechanisms. Based on the theory of rationalization defense mechanism, a 2 × 2 purchase channel matrix of online and offline purchase, online consultation, and the offline experience was constructed to explore the influence of consumers’ tolerance of product quality and brand on their purchase channel choice. The results show that: (1) consumer product tolerance positively influences consumers’ online purchasing choice; (2) consumer product tolerance influences purchase channel choice through rationalization; and (3) the sweet lemon mechanism mediates consumer product tolerance on online consultation and online purchase and offline experience, but the sour grapes mechanism does not mediate.